Junior Worldmark encyclopedia of world holidays. Volume 2, Easter, Halloween and Festivals of the Dead - Griffin, Robert H., 1951-; Shurgin, Ann H., 1952- (Detroit : UXL, 2000)
Provides general overviews of two holidays celebrated in thirty countries around the world, including Easter and Halloween and Festivals of the Dead; and contains details on how each holiday is observed in one or more countries, discussing the history, stories, customs, clothing or costumes, food, arts and games, symbols, and music associated with each celebration.
Includes bibliographical references and index.
5-8
Keywords: Festivals -- Encyclopedias, Juvenile; Holidays -- Encyclopedias, Juvenile; Encyclopedias and dictionaries; Festivals -- Encyclopedias; Holidays -- Encyclopedias; Encyclopedias and dictionaries; Festivals -- Encyclopedias; Holidays -- Encyclopedias